2023
DOI: 10.1021/acs.cgd.3c00950
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Hydrogen-Bonded Networks Formed by Sulfate and Bisulfate Salts of Benzenetetramines

Johann O. E. Sosoe,
Thierry Maris,
James D. Wuest

Abstract: Benzenetetramines, like other aromatic compounds with multiple NH2 groups, are easily oxidized and are attractive candidates for use as components of redox-active organic materials. However, many aspects of the chemistry of benzenetetramines and related compounds remain poorly understood, such as the nature of their salts and their preferred patterns of association, which determine how they can be used to construct predictably ordered redox-active solids. To provide relevant new information, we have studied a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The resulting precipitate was separated by filtration, washed with cold EtOH, and dried in a vacuum to give the sulfate salt of benzene-1,2,3,4-tetramine ( 7 ·H 2 SO 4 ) as a crystalline solid (0.72 g, 3.0 mmol, 37% overall yield): 1 H NMR (400 MHz, D 2 O containing added DCl to increase solubility) δ 6.78 (s, 2H); 13 C­{ 1 H} NMR (101 MHz, D 2 O) δ 126.5, 121.3, 117.7. The structure of the product was confirmed by single-crystal X-ray diffraction …”
Section: Computational and Experimental Methodsmentioning
confidence: 99%
“…The resulting precipitate was separated by filtration, washed with cold EtOH, and dried in a vacuum to give the sulfate salt of benzene-1,2,3,4-tetramine ( 7 ·H 2 SO 4 ) as a crystalline solid (0.72 g, 3.0 mmol, 37% overall yield): 1 H NMR (400 MHz, D 2 O containing added DCl to increase solubility) δ 6.78 (s, 2H); 13 C­{ 1 H} NMR (101 MHz, D 2 O) δ 126.5, 121.3, 117.7. The structure of the product was confirmed by single-crystal X-ray diffraction …”
Section: Computational and Experimental Methodsmentioning
confidence: 99%
“…For example, Wuest and coworkers demonstrated how various redox-active benzene tetramine isomers crystalize. 52 They found that they could direct the resultant crystalline structure of these salts by engineering the H-bonding environment. Later, Wuest and coworkers showed how more complex benzoquinone-hydroquinone cocrystals could be generated by synergistic hydrogen bonds between these redox-active units.…”
Section: Hydrogen Bondingmentioning
confidence: 99%
“…In fact, the HSO 4 − anion may serve the latter role well – several organic and inorganic sulfate-hydrogen sulfate mixed-anion systems have been reported with strong (SO 4 ⋯HSO 4 ) 3− hydrogen bonds (O⋯O <2.5 Å, H⋯H ≪1.5 Å). 23–26…”
Section: Introductionmentioning
confidence: 99%